A Clinical Study of HBsAg‐Activated Dendritic Cells and Cytokine‐Induced Killer Cells During the Treatment for Chronic Hepatitis B. (12th September 2013) - Ma, Y.‐J.; He, M.; Han, J.‐A.; Yang, L.; Ji, X.‐Y.
Abstract We aim to study the therapeutic effects of HBsAg‐activated DCs and cytokine‐induced killer (CIK) cells as adoptive immunotherapy in patients with Chronic Hepatitis B (CHB). Autologous HBsAg‐activated DC–CIK cells were infused into patients with CHB to evaluate their effect on HBV‐DNA, HBsAg, ALT, etc. The viral load in the treatment group decreased significantly (P < 0.001), while that in the control group did not decrease (P > 0.05). Twenty‐one patients (63.6% efficiency) in the treatment group had a viral response (≥2 log decrease in viral load), while four patients (14.8% efficiency) from the control group had a viral response. There were significant differences in the viral responses of the two groups (the control group 63.6% versus the control group 14.8%, P < 0.001). We concluded that the immunity was enhanced after HBsAg activation in DCs and CIK cells. Reinfusion of autologous HBsAg‐activated DC–CIK cells inhibited HBV proliferation in 21 of 33 (63.6%) patients.